PEMANFAATAN BAHAN ALAMI UNTUK PENGEMBANGAN PRODUK ECOPRINT DI DUKUH IV CERME, PANJATAN, KABUPATEN KULONPROGO - Endah Saptutyningsih; Dyah Titis Kusuma Wardani (WARTA LPM, 2019)
The Community Partnership Program aimed to provide direct benefits to people's lives in the social and economic fields and to improve the quality of resources through the empowerment of the women of the PKK and Karang Taruna groups in Dukuh IV Cerme, Panjatan, Kulon Progo Regency by utilizing natural ingredients in around his residence. This activity was expected to solve the problems in the partner villages, namely the source of income for the community is only dominated by the agricultural sector, the natural potential of the village that has not been used properly, lack of skills in managing the potential of the village, the majority of the residents of Dukuh VI Cerme are housewives who have minimal income. The Community Partnership Program consists of two activities, namely the training in making ecoprints by utilizing natural materials in the neighborhood around Dukuh VI Cerme, Panjatan and making audio-visual videos on how to make ecoprints. The Partnership Program activity is expected to be carried out continuously so that it can be an additional livelihood for the local community because the selling value of the ecoprint product is still quite high on the market. Keywords: Ecoprint; Income; Natural Ingredient; Kulonprogo